Recent progress on mass transport related processes in engineering materials - Öchsner, Andreas; Murch, G. E.; Shokuhfar, Ali; Delgado, João M. P. Q. (Diffusion and defect data. Defect and diffusion forum, 2020)
Special topic volume with invited peer reviewed papers only.